Construction of the Legal Position of the Religious Affairs Office in Handling Early Marriage from the Perspective of Maqasid Usrah Jamaluddin 'Atiyyah - Ibnu Aly Ismail; Sugianto Sugianto; Ahmad Rofii (INKLUSIF (JURNAL PENGKAJIAN PENELITIAN SYARIAH DAN ILMU HUKUM), 2025)
Early marriage is often motivated by economic, educational, and cultural factors. The Religious Affairs Office's efforts to prevent early marriage are less effective due to differences in perspectives between religion and the state. This study examines the legal position of the Religious Affairs Office in addressing early marriage in Sokaraja District and explores the views of maqashid al-usrah in preventing early marriage. Using a normative descriptive approach, the study found that early marriages in Sokaraja District were 29 cases in 2020, 23 cases in 2021, 40 cases in 2022, and 13 cases in 2023, representing a 67% decrease. The Sokaraja District Religious Affairs Office has socialized Law Number 16 of 2019 concerning marriage, which sets the ideal age limit for marriage at 19 years. This law considers legal psychological, biological, and other aspects. From a maqashid al-usrah perspective, the aim is to protect children's rights, maintain family structure, and support community welfare. The Office of Religious Affairs' efforts to prevent early marriage align with these goals. By socializing the marriage law and promoting awareness, the office contributes to achieving the objectives of maqashid al-usrah.